(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
This Study Sought to Determine The Relationship and Impact Between The Tax Core Capabilities and Tax Settlement The Study Took Place in The Tax Administration, and Based The Problem Was to Two Hypotheses As Solutions Initial Mocked Content to Explain The Relationship Between The Phenomena, and to Test The Validity of Assumptions And Due To The Fact That The General Authority for Taxes is The Body for The Advancement of The Collection Tax In Iraq Random Sample Was Selected to Represent The Population of The Study, Since The Sample Included 22 Individuals Representing 70% of The Total Community to Study, Represented by The Director General, Agents and Directors of Departments and Branch Managers Managers Working in The General Authority for Taxes, Has Been Gathering Information About The Sample Using The Questionnaire Form and Process Data Using A Combination of Statistical Methods to The Study of The Relationship Between Research Variables Depending on The Program SPSS to Get to The Results, as Well as Personal Interviews Conducted by The Researcher ، In Light of The Analysis Results That Showed The Health of Hypotheses Logical What Construct Him and The Validity of What Outcome Him And Confirmed That It Closed The Gap Study Intellectual Dilemma And Applied Problem While The Study Found A Set of Conclusions was The Most Important of The Existence of The Effect of The Relationship Between The Tax Core and The Tax Collection Performance Capabilities, Based on The Conclusions Redeem Find A Set of Recommendations, Most Notably: Verily Pursue Tax Bases in The Core Work is Estimators Would Achieve Compliance with Policies, Plans, According to The What is The Decree and Thus Increase Tax Collection.